Role of cavities and hydration in the pressure unfolding of T(4) lysozyme - Nucci, Nathaniel V. (National Academy of Sciences, 2014)
It is well known that high hydrostatic pressures can induce the unfolding of proteins. The physical underpinnings of this phenomenon have been investigated extensively but remain controversial. Changes in solvation energetics have been commonly proposed as a driving force for pressure-induced unfolding. Recently, the elimination of void volumes in the native folded state has been argued to be the principal determinant. Here we use the cavity-containing L99A mutant of T(4) lysozyme to examine the pressure-induced destabilization of this multidomain protein by using solution NMR spectroscopy. The cavity-containing C-terminal domain completely unfolds at moderate pressures, whereas the N-terminal domain remains largely structured to pressures as high as 2.5 kbar. The sensitivity to pressure is suppressed by the binding of benzene to the hydrophobic cavity. These results contrast to the pseudo-WT protein, which has a residual cavity volume very similar to that of the L99A–benzene complex but shows extensive subglobal reorganizations with pressure. Encapsulation of the L99A mutant in the aqueous nanoscale core of a reverse micelle is used to examine the hydration of the hydrophobic cavity. The confined space effect of encapsulation suppresses the pressure-induced unfolding transition and allows observation of the filling of the cavity with water at elevated pressures. This indicates that hydration of the hydrophobic cavity is more energetically unfavorable than global unfolding. Overall, these observations point to a range of cooperativity and energetics within the T(4) lysozyme molecule and illuminate the fact that small changes in physical parameters can significantly alter the pressure sensitivity of proteins.